(untitled) - Jan Bell (London, 1992)
This book represents a new approach to skills teaching and which integrated skills activities bring together reading, writing, listening and speaking in a natural and realistic way. It contains: Grammar practice and vocabulary building; Reading comprehensive; Composition and guided writing; Listening comprehension; Includes exercises useful for the First Certificate Examination; Self-study edition with answer key
Keywords: english language - study and teaching